Determination of the Effectiveness of Different Spraying Programs Against Powdery Mildew Disease (Erysiphe necator Schw.) in Vineyard - Ümit ESER; Abdullah BALTACI (ISPEC Journal of Agricultural Sciences)
This study was carried out to determine the first spraying time and other spraying intervals in the chemical control against the disease and to establish a spraying program that will be effective in the control of the disease. The study was carried out in 2015 in a farmer's vineyard of 5 da of Razakı grape variety in Taşova district of Amasya province in a randomized block design with 4 treatments and 5 replications. In the study, treatments with different spraying times and intervals were applied for the control of the disease. At the end of the study, the effects of these treatments on the control of the disease were statistically evaluated and the most successful spraying program was determined. The same fungicide containing 100 g l-1 Kresoxim-Methyl+200 g l-1 Boscalid active ingredient was used in all treatments. According to the statistical analyses and evaluations, all treatments were found to be effective in the chemical control of powdery mildew on both leaves and clusters. However, due to reasons such as economic losses, environmental health and resistance problems in systemic drugs, it is thought that the application with the lowest number of sprayings and the highest effect of 91.96 % on panicle and 87.52 % on leaf should be considered.